A Comparison Between Hyclone And Biowest: Effects To Human MSCs Proliferation, Morphology, And Osteogenic Differentiation - Saskianti, Tania; Misami, Kanawa; Kato, Yukio (Journal of Tropical Life Science, 2013)
Mesenchymal stem cells (MSC) are expanded in a basal culture medium supplemented with fetal bovine serum (FBS) with or without additional growth factors. The serum contains basic components such as hormones and growth factors which provide robust MSC proliferation. However, the effects of different serum in the isolation and proliferation of primary MSC remains unclear. In this study we compared effect of serums on stimulating MSC proliferation and osteogenic differentiation. Therefore we evaluated the impact of Hyc1 and Bw1 containing medium on primary MSC morphology. Primary MSC grown in both serum containing medium retain the ability to differentiate into osteoblast. Bw1 containing serum showed slightly, unsignificanty higher potential as compared to Hyc1. However more detailed analysis on the composition of each serum on overall MSC morphology and proliferation must be further explored. The result of this study should form a basis for further studies examining specific substance needed in MSC proliferation and differentiation in more detail.